USAGE OF SAVSOFT QUIZ APPICATION FOR THE DARING ASSESMENT ON LEARNING OF CHEMISTRY SUBJECT IN SMA NEGERI 2 PALANGKA RAYA - Nopriawan Berkat Asi; Maya Erliza Anggraeni; Syarpin Syarpin; Anggi Ristiyana Puspita Sari; Yamine Yasmine (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
The activity of Community Development & Empowerment is aiming to train high school teachers in using the Savsoft Quiz application as the assessment tool in daring learning for chemistry subject in High School level. This training was been implemented in SMA Negeri 2 Palangka Raya since September 2021 which were participated by 5 (five) teachers for chemistry subject. The training method we applied was discussion model and exercise. In this section, some teachers were trained to manage the students and classes, to design the assessment questions-multiple choice, to develop the question bank, to manage the quize/exercise/assignment/test, and reporting the those final results. Our project results display that from 5 (five) teachers for chemistry subject in SMA Negeri 2 Palangka Raya are capable to complete all tasks and assignments which were given then we provided the training certivicate to them as the proof of their training results.